Effect of digestive enzymes and pH on variation of bioavailability of green tea during simulated in vitro gastrointestinal digestion - Wei Qin; Sunantha Ketnawa; Yukiharu Ogawa (Food Science and Human Wellness)
To examine the effect of digestive attributes such as digestive enzymes and pH on changes in phenolic compound content and antioxidant activity during digestion, the bioavailability of green tea infusion was investigated using a simulated in vitro gastrointestinal digestion model. The total polyphenol content (TPC) decreased to 65%–70% throughout the mimicked normal digestion (MD) compared to the initial value. The total flavonoid content (TFC) decreased to approximately 25% after starting the gastric stage (pH 1.2); however, it regained to approximately 60% in the intestinal stage (pH 6.8). The mimicked digestive condition without digestive enzymes (WOE), which followed only the pH conditions of MD, showed significantly lower TPC and TFC values than MD. The percentage of antioxidant activity based on the initial values indexed by DPPH, ABTS, and FRAP gradually declined from approximately 60% at the gastric stage to approximately 40% at the final digestion stage. Meanwhile, the percentage of residual MIC was around 50% at the gastric stage. However, it gradually increased at the intestinal stage. The significantly lower antioxidant activity showed for WOE than MD throughout the simulated digestion. This study demonstrated that digestive enzymes and pH play a crucial role in the bioavailability of green tea infusion.